When multiplying powers with the same base, we need to use the Product of Powers Rule which states a^m⋅a^n=a^m+n. This rule is stating that we add the exponents and keep the base the same.

Since \(\displaystyle{\left(−{1.5}\right)}={\left(−{1.5}\right)}^{{{1}}}\), then using the Product of Powers Rule gives:

\(\displaystyle{\left(−{1.5}\right)}^{{{11}}}\times{\left(−{1.5}\right)}={\left(−{1.5}\right)}^{{{11}}}⋅{\left(−{1.5}\right)}^{{{1}}}={\left(−{1.5}\right)}^{{{11}+{1}}}={\left(−{1.5}\right)}^{{{12}}}\)

Since \(\displaystyle{\left(−{1.5}\right)}={\left(−{1.5}\right)}^{{{1}}}\), then using the Product of Powers Rule gives:

\(\displaystyle{\left(−{1.5}\right)}^{{{11}}}\times{\left(−{1.5}\right)}={\left(−{1.5}\right)}^{{{11}}}⋅{\left(−{1.5}\right)}^{{{1}}}={\left(−{1.5}\right)}^{{{11}+{1}}}={\left(−{1.5}\right)}^{{{12}}}\)